Why Ni is absent from the surface of La2NiO4+δ?. Issue 47 (30th October 2015) - Wu, Ji; Pramana, Stevin S.; Skinner, Stephen J.; Kilner, John A.; Horsfield, Andrew P.
Abstract : The calculated Gibbs reaction energy of La2 NiO4 decomposition (left) and the proposed resulting layered structure (right) provide an explanation for the experimentally observed Ni-absent surfaces and Ni-enriched subsurface layers on La2 NiO4 . Abstract : La2 NiO4+ δ (LNO214) is a potential intermediate temperature solid oxide fuel cell (IT-SOFC) cathode material which belongs to the Ruddlesden–Popper (RP) structure series A n +1 B n O3 n +1 . There is interest in this material as it offers a way to avoid Sr segregation and associated degradation, as LNO214 can take in oxygen interstitials and become catalytically active without A-site doping. While the bulk ionic conduction mechanisms are well studied, its surface structure and chemistry are still a matter of debate. Recent experimental studies (both with and without dopants) reveal that it has a La-terminated surface and a highly Ni deficient surface layer. These results disagree with previous computer simulations, and undermine the conventional explanation for the oxygen reduction process at the surface. In this work we evaluate the thermodynamic stability of La2 NiO4+ δ at IT-SOFC operation temperatures. We find that the decomposition of La2 NiO4+ δ to produce La2 O3 and higher order RP phases is indeed thermodynamically favourable. A hypothesis for the formation mechanism of the La-terminated and Ni deficient surface based on partial decomposition and surface passivation is proposed and evaluated.